EDUCATION ON CLEAN AND HEALTHY LIVING BEHAVIOR TO OPTIMIZE THE LEVEL OF AWARENESS OF PERSONAL AND ENVIRONMENTAL CLEANLINESS IN TAQWA AL-QOLBI ORPHANAGE - Yuliasari, Elly; Adilah Nafiisah; Aradea Putri Ayu Wardani; Mayravanya Zakiya Eka Restu; Fahriah Firda Syahira (Inovasi Lokal, 2025)
Clean and Healthy Living Behavior (PHBS) is a form of manifestation of healthy living orientation in individual, family and community culture, which has the aim of improving, maintaining and protecting health both physically, mentally, spiritually and socially. Clean and Healthy Living Behavior is a manifestation of a healthy living orientation that must be instilled from an early age so that it becomes a habit. The reason behind the selection of Clean and Healthy Living Behavior material from this activity is the existence of problems in Orphanages related to the lack of understanding and awareness of orphanage children to carry out Clean and Healthy Living Behaviors. The aim of this outreach activity is to increase awareness of healthy and clean living behavior among children at the Taqwa Al-Qolbi orphanage. The implementation of socialization activities at the LKSA Taqwa Al-Qolbi Orphanage, Malang City, will be held on Sunday, December 3 2023. The method for implementing this socialization activity is in the form of offline counseling with powerpoint and video as educational material. The material that researchers convey includes washing hands, how to tidy up clothes, advice on bathing, the dangers of frequently consuming sweet drinks, the importance of drinking water, throwing rubbish in the right place, and regular exercise and its benefits. The results of the socialization activities that have been carried out show that children's knowledge and understanding of PHBS has increased by 22.5%.